Standard specification for copper brazed steel tubing. (American Society for Testing and Material, 2008)
This specification covers double-wall, copper-brazed steel tubing suitable for general engineering uses, particularly in the automotive, refrigeration, and stove industries for fuel lines, brake lines, oil lines, heating and cooling units, and the like.